In Vitro Bioassay-guided Isolation of Radioprotective Fractions from Extracts of Pinus koraiensis Bark - Yun, Keli (Pharmacogn Mag, 2017)
OBJECTIVE: The aim of this study was to evaluate radioprotective effect of extracts of Pinus koraiensis bark and its fractions on rat splenocytes by using bioassay-guided isolation in order to obtain the best active fraction. MATERIALS AND METHODS: P. koraiensis bark was ground and extracted with water, 40% acetone, 95% ethanol. Bio-guided assay was selected as an evaluation method to further fractionate radioprotective component from P. koraiensis bark extract. Total phenolic and flavonoid contents in fractions were also measured. Rat splenocytes were prepared by using mechanical trituration method. DNA damage was assessed as comet parameters (tail DNA%, tail length, tail moment, olive tail moment). The levels of malondialdehyde (MDA), and activity of superoxide dismutase (SOD), catalase (CAT) in cultured rat splenocytes were also measured. RESULTS: The radioprotective effects decreased from rutin >95% ethanol extracts of Pinus koraiensis bark (95EEP) >40AEP > WEP. The stimulating effects decreased from rutin > n-butanol extract (NBE) > EAE. The results demonstrate that there exists toxic ingredients (PEE and dichloromethane extract), proliferative-promoting, radioprotective component (EAE and NBE) in 95EEP. fraction eluted from n-butanol fractions of 95EEP with 50% methanol solution (NBEPKB-50ME), a fraction of NBE result from bio-guided isolation, demonstrates good radioprotective efficacy on rat splenocytes. NBEPKB-50ME pretreated rat splenocytes demonstrated progressively reduced levels of MDA when compared with γ-ray exposed cells. Different dose of NBEPKB-50ME pretreatment with 8 Gy-irration showed an increase in enzymatic antioxidant. CONCLUSIONS: Proliferative-promoting efficacy, radioprotective effect of different solvents extracts of the bark of P. koraiensis were investigated in this work. NBEPKB-50ME was the best elution in NBE, especially in restoring SOD, CAT activities, content of GSH, decreasing DNA damage. SUMMARY: The radioprotective effects decreased from rutin > 95EEP > 40AEP > WEP. The extract of Petroleum ether, dichloromethane extract (DME) of 95% ethanol extract of P. koraiensis (PEE, DME) show toxic effect on rat splenocytes. The extract of Ethyl acetate, n-butanol extract of 95% ethanol extract of P. koraiensis (EAE, NBE) show proliferative-promoting, radioprotective effect on rat splenocytes. Single-cell gel electrophoresis was used to evaluate the spleen cell DNA damage parameters affected by gamma-radiation and addition of best component NBEPKB-50Me from extract of P. koraiensis bark. NBEPKB-50ME pretreatment with 8 Gy-irradiation showed an increase in enzymatic antioxidant capacity. NBEPKB-50ME pretreated (80, 160, 320, 480 mg/ml) rat splenocytes demonstrated progressively reduced levels of MDA when compared with g-ray exposed cells. [Image: see text] Abbreviations used: MDA: Malondialdehyde; SOD: Superoxide dismutase; CAT: Catalase; PEE: Petroleum ether Extract; DME: Dichloromethane extract; EAE: Ethyl acetate extract; NBE: n-butanol extract; WAP: Water extracts of Pinus koraiensis bark; 40AEP: 40% acetone extracts of Pinus koraiensis bark; 95EEP: 95% ethanol extracts of Pinus koraiensis bark; TPC: Total phenolic content; TFC: Total flavonoid content; NBEPKB-50ME: Fraction eluted from n-Butanol fractions of 95EEP with 50% methanol solution.